Assessment of residual styrene monomer migration into yoghurt packed in high impact polystyrene pots using a modelling approach - Naziruddin, M. A.; Nurulhuda, K.; Sulaiman, R.; Sanny, M. (Elsevier, 2023)
The first objective of this study was to quantify the migrated styrene levels from High Impact Polystyrene (HIPS) pots into yoghurt during shelf-life. The second objective was to assess the styrene migration trend with respect to time and determine the migration parameters: diffusion coefficient (D) and partition coefficient (KFP) by fitting the experimental data to a migration model. Three different brands of plain stirred yoghurt packed in HIPS pot (Y1, Y2, and Y3) were purchased from established manufactures. Migration experiments were conducted at refrigerated conditions (ˆ¼4 °C), and samples were analysed on day zero and every four days until the products expired. The levels of migrated styrene in all three yoghurts ranged from 5.740 ± 0.008 to 78.39 ± 0.42 ng/g throughout the 672 h migration test. The final migrated styrene levels were equivalent to 83.55“95.89 of the initial styrene content in its respective HIPS pots. The levels of detected styrene in all yoghurts were below the overall migration limit (OML) specified by the European Commission in Regulation (EU) No October 2011 at 10 mg/dm2. The models predicted that the styrene migration into all yoghurts would reach equilibrium from 2400 to 7920 h after end of shelf life. This study finds Y3 with the highest D (6.788 — 10ˆ’11 cm2 sˆ’1) despite having the lowest KFP (0.227) and fat content (1.5) compared to the other yoghurts, which contradict with claims from previous studies. The determined D for Y1 and Y2 were 3.047 — 10ˆ’11 and 4.924 — 10ˆ’11 cm2 sˆ’1, respectively. Meanwhile, KFP for Y1 and Y2 were 0.865 and 0.477, respectively. Based on this study, we found uncertainty in estimating values of D in actual food because unlike simulant, food has expiry dates and may change in characteristics over time.